Potret Nomophobia (No Mobile Phone Phobia) di Kalangan Remaja - Widyastuti, Dian Ari; Muyana, Siti (Jurnal Fokus Konseling, 2018)
This study aims to obtain a description of the condition of nomophobia among adolescents. This study uses a quantitative approach to the type of descriptive research. The sample in this study amounted to 540 students of SMK taken by using simple random sampling technique. The data collection instrument used for this study using nomophobia scale and data analysis is done by using standard deviation and mean. The results showed that the use of mobile phone among adolescents who showed nomophobia levels in very high category of 5%, high category 31%, medium category 35%, low category 24 %, and very low category 5%.Keywords: Nomophobia, Mobile Phone